Qurʾanic Scholarly Authority Within Pesantren Networks in Indonesia: A Genealogical Reading of the Sanad of KH Munawwar Sidayu, Gresik - Hidayati, Nurul (QOF, 2025)
This study examines the formation of scholarly authority within the network of tahfiz pesantren through the Qur’anic sanad of KH Munawwar Sidayu in Gresik, which plays a pivotal role in preserving the tahfiz tradition. The research focuses on mapping the socio-intellectual and genealogical dynamics of the pesantren, as well as the interplay between knowledge, power, and epistemic legitimacy in a local context that has received limited academic attention. A qualitative approach with a genealogical method, enriched by the social history of pesantren, was employed. Data were collected through in-depth interviews with caretakers, teachers, and students; participatory observation; and examination of pesantren archives, sanad documents, and historical literature. Interpretative-genealogical analysis, grounded in Michel Foucault’s theory of power/knowledge, revealed the mechanisms of authority distribution and knowledge legitimization. Findings indicate that the sanad network, kinship relations among kyai, and collaboration with alumni and community institutions create a structured and sustainable scholarly authority system. The sanad serves as a conduit for epistemic and moral legitimacy, familial ties reinforce socio-intellectual continuity, and alumni act as agents of knowledge dissemination. Engagement with governmental and societal institutions extends the pesantren’s influence, positioning it as both a center for knowledge production and reinforcement of Qur’anic tradition. This study contributes a genealogical analytical model of tahfiz pesantren networks, enriching scholarship on intellectual networks and the legitimacy of Qur’anic knowledge transmission in Indonesia.